SHORT-TERM EFFICACY OF INTRAVITREAL PATIZRA® (RANIBIZUMAB) IN TREATMENT NAIVE PATIENTS- REAL WORLD EVIDENCE IN PAKISTAN - Malik, Hajra Arshad; Sabih, Rayyan; Khan, Hina; Muhammad Umair,; Muhammad Asif,; Asrar, Aamir; Asrar, Maha (Journal of Ayub Medical College Abbottabad, 2022)
Background: Macular oedema is a final common pathway of a multitude of both ocular and systemic insults. This study was conducted to evaluate the short-term efficacy and safety of intraocular Ranibizumab in patients with macular oedema in a '˜real-world' setting in Pakistan. Methods: A prospective multicenter study conducted at Amanat Eye Hospitals in Islamabad and Rawalpindi from 1st August 2018 to 1st November 2019. Forty-four eyes of 34 patients with macular oedema were treated with monthly intravitreal Ranibizumab (Patizra®) injections for three consecutive months. Best-corrected visual acuity (BCVA), and optical coherence tomography (OCT) parameters including central retinal thickness (CRT) and macular volume were assessed prior to the injections and then 4 weeks post the final injection and compared. Results: BCVA improved from logMAR 0.61±0.40 at baseline to 0.27±0.35 four weeks after the third intravitreal injection. CRT decreased from 428.54±187.06Î¼m at baseline to 364.50±170.49 Î¼m. Macular volume showed a non-significant decrease from 9.97±3.19 mm3 at baseline to 9.22±2.68 mm3 four weeks after the third intravitreal injection. No systemic or ocular complications were observed during the course of the study. Conclusion: Treatment with intravitreal Patizra® injections was found safe and resulted in clinically and statistically significant improvement in visual acuity and the SD-OCT parameter of central retinal thickness in patients with macular edema secondary to various retinal pathologies. There was no significant decrease in the macular volume.